2016
DOI: 10.1016/j.smrv.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related epileptic behaviors and non-REM-related parasomnias: Insights from stereo-EEG

Abstract: During the last decade, many clinical and pathophysiological aspects of sleep-related epileptic and non-epileptic paroxysmal behaviors have been clarified. Advances have been achieved in part through the use of intracerebral recording methods such as stereo-electroencephalography (S-EEG), which has allowed a unique "in vivo" neurophysiological insight into focal epilepsy. Using S-EEG, the local features of physiological and pathological EEG activity in different cortical and subcortical structures have been be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 183 publications
(243 reference statements)
5
72
0
Order By: Relevance
“…In this sense, the localized coexistence of sleep and wake-like EEG activity observed in sleepwalkers may reflect a deregulation of an intrinsic property of the brain that can culminate in clinical episodes of somnambulism in predisposed individuals. 66 Relatedly, one study of pre-arousal EEG activity in adult sleepwalkers showed that increased SWA and slow oscillation density was specific to clinical episodes rather than generalized to all sleep-wake transitions. 17 It would thus be of interest to investigate the extent to which the patterns of EEG functional connectivity observed in the present study are specific to somnambulistic episodes.…”
Section: Limitations and Implication For Future Studiesmentioning
confidence: 99%
“…In this sense, the localized coexistence of sleep and wake-like EEG activity observed in sleepwalkers may reflect a deregulation of an intrinsic property of the brain that can culminate in clinical episodes of somnambulism in predisposed individuals. 66 Relatedly, one study of pre-arousal EEG activity in adult sleepwalkers showed that increased SWA and slow oscillation density was specific to clinical episodes rather than generalized to all sleep-wake transitions. 17 It would thus be of interest to investigate the extent to which the patterns of EEG functional connectivity observed in the present study are specific to somnambulistic episodes.…”
Section: Limitations and Implication For Future Studiesmentioning
confidence: 99%
“…Video-EEG-PSG captured seven nocturnal seizures (four hypermotor and three PA), all occurring during REM sleep. However, some of these arousals may be surface-negative seizures which would be apparent upon stereoelectroencephalography (SEEG) (Gibbs et al, 2016). In our epilepsy and sleep disorder centre, this is the first case of SHE we have encountered which occurred during REM sleep.…”
Section: Discussionmentioning
confidence: 84%
“…However, these studies were conducted on scalp EEG, whereas we used intracranial EEG. This difference is important, as works using simultaneously extra- and intracranial recording have shown that only a fraction of IS are detected on the scalp (12, 13). The reason why IS seem to propagate better during deep sleep remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we defined the “spatial instability” as the standard variation of RDP across the different channels. The motivation for using this measure was the well-known fact that delta-sleep can be a local process (1315). Here also, we found a positive correlation between instability and ISR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation